Wskazania wychowawcze w ujęciu Lucjusza Anneusza Seneki (4 a. Chr. - 65) i w pismach apologetycznych św. Augustyna (354-430) - Swoboda, Antoni (Verbum Vitae, 2012)
The article consists of four parts. The first part presents the educational process evaluated by Seneca and Augustine. Then their opinion about the educational environment is examined. The third part explains the educational aims such as religious, moral and intellectual upbringing developed  in the writings of Seneca and Augustine. At the end the educational methods of both authors are depicted.